The Evaluation of Structural, Electrical and Magnetic Properties of Samarium substituted Spinel Ferrites. Issue 1 (1st January 2021) - Shah, Muhammad Shakil; Aman, Salma; Ahmad, Naseeb; Tahir, Muhammad Bilal; Alrowaili, Z. A.; Al-Buriahi, M. S.; Farid, Hafiz Muhammad Tahir; Khosa, Rabia Yasmin; Hussein, Enas E.; Elnaggar, Ashraf Y.; El-Bahy, Zeinhom M.
Abstract : The spinel ferrites have been manufacturing long time because of their variety of applications in technological and industrial field. In the following study, the samarium doped spinel ferrites were under examination. The prepared compositions were denoted as; SrSm x Fe2– x O4, x  = 0, 0.025, 0.05, 0.075, 0.10. Sol–gel procedure was employed to make these samples. All the samples were investigated through the X-ray diffraction technique. The phase of prepared product was detected for the first three samples. However, the orthorhombic phase, that is, SmFeO3, was traced when samarium (Sm) composition reached 0.075 and above. The smaller width of the M–H loop confirmed the formation of soft ferrites. Saturation and remanence values were diminished with the substitution of samarium ions. But the anisotropy constant as well as coercivity values was enhanced with the samarium contents. Above mentioned features of spinel ferrites showed their possible usage in high-density recording applications.